Implementasi Bimbingan dan Konseling dalam Suasana Pendidikan - Husni, Muhammad; Hasyim, Muhammad (Institute Agama Islam Al-Qolam Malang, 2020)
Abstract Guidance and counseling should be adjusted to the problems faced by students so that guidance assistance can achieve the right goals and expected goals in the guidance. This research method uses qualitative descriptive research. The aim is to analyze and find the concept of implementation of guidance and counseling as learning motivation. The results of the study that the concept of implementation of guidance and counseling as a form of learning motivation provides facilities and infrastructure as well as experts in the field of guidance and counseling. Types of services in the form of tutoring, career guidance, and case guidance.